Rapid emergence of African swine fever virus variants with different numbers of a tandem repeat sequence in South Korea. Issue 4 (6th November 2020) - Kim, Seon‐Hee; Lee, Song‐I; Jeong, Hyun‐Gi; Yoo, Jongchan; Jeong, Hyesung; Choi, Yongjun; Son, Kidong; Jheong, Weon‐Hwa
Abstract: African swine fever virus variants with different numbers of a 10‐bp tandem repeat were isolated in South Korea soon after being identified in wild boar. The short emergence periods and sympatric distributions within a narrow geographical region suggest that the variants were sporadically generated in the pre‐existing viral population.